Gestational Hypoxia and Blood-Brain Barrier Permeability: Early Origins of Cerebrovascular Dysfunction Induced by Epigenetic Mechanisms - Herrera, Emilio A.; González-Candia, Alejandro (Frontiers in Physiology, 2021)
Fetal chronic hypoxia leads to intrauterine growth restriction (IUGR), which is likely to reduce oxygen delivery to the brain and induce long-term neurological impairments. These consequences indicate a modulatory role for oxygen in cerebrovascular development. During intrauterine hypoxia, the fetal circulation suffers marked adaptations known as the 'brain-sparing phenotype.' This is a well-characterized response. However, little is known about the postnatal course and consequences of this fetal cerebrovascular adaptation. Many neurodevelopmental disorders of motor and cognitive function have their origins in the antenatal period. Still, few studies have focused on how intrauterine fetal hypoxia interferes with normal brain development of the blood-brain barrier (BBB) in the IUGR neonate. The BBB is centrally positioned within the neurovascular unit (NVU) and is formed by a monolayer of endothelial and mural cells. The BBB prevents neurotoxic molecules, plasma components, blood cells, and pathogens, among others, from entering the brain. At the same time, the BBB regulates the transport of molecules into and out of the central nervous system (CNS) by a highly selective permeability system. In cerebrovascular diseases, BBB breakdown and dysfunction lead to leakages of components into the CNS, contributing to neurological deficits. The fetal brain circulation is particularly vulnerable in IUGR and is proposed to be one of the main pathological processes deriving BBB disruption. However, few studies are available about this topic, and the small body of evidence shows controversy. Therefore, in this mini-review, we analyze the BBB permeability-associated mechanisms in the brain exposed to chronic intrauterine hypoxia.